Whole-body dynamic imaging with continuous bed motion PET/CT. Issue 4 (April 2016) - Osborne, Dustin R.; Acuff, Shelley
Abstract : Most dynamic imaging protocols require long scan times that are beyond the range of what can be supported in a routine clinical environment and suffer from various difficulties related to step and shoot imaging techniques. In this short communication, we describe continuous bed motion (CBM) imaging techniques to create clinically relevant 15 min whole-body dynamic PET imaging protocols. We also present initial data that suggest that these CBM methods may be sufficient for quantitative analysis of uptake rates and rates of glucose metabolism. Multipass CBM PET was used in conjunction with a population-based input function to perform Patlak modeling of normal tissue. Net uptake rates were estimated and metabolic rates of glucose were calculated. Estimations of k3 ( K i / V d ) were calculated along with modeling of liver regions of interest to assess model stability. Calculated values of metabolic rates of glucose were well within normal ranges found in the previous literature. CBM techniques can potentially be used clinically to obtain reliable, quantitative multipass whole-body dynamic PET data. Values calculated for normal brain were shown to be within previously published values for normal brain glucose metabolism.